2020
DOI: 10.1111/jdv.17035
|View full text |Cite
|
Sign up to set email alerts
|

Association between the dermoscopic morphology of peripheral globules and melanocytic lesion diagnosis

Abstract: Background The presence of peripheral globules is associated with enlarging melanocytic lesions; however, there are numerous patterns of peripheral globules distribution and it remains unknown whether specific patterns can help differentiate enlarging naevi from melanoma. Objective To investigate whether morphological differences exist between the peripheral globules seen in different subsets of naevi and in melanoma. Methods A cross‐sectional study of clinical notes that mentioned peripheral globules, in addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 14 publications
3
22
0
Order By: Relevance
“…Reiter et al 6 did not include lesions with pseudopods in their study. While pseudopods are also round or oval structures that project outwards from the edge of lesions, they are not globules in the strict sense of the word (the last edition of the Merriam-Webster dictionary defines globule as "a tiny globe or ball especially of a liquid").…”
Section: Commentmentioning
confidence: 95%
See 1 more Smart Citation
“…Reiter et al 6 did not include lesions with pseudopods in their study. While pseudopods are also round or oval structures that project outwards from the edge of lesions, they are not globules in the strict sense of the word (the last edition of the Merriam-Webster dictionary defines globule as "a tiny globe or ball especially of a liquid").…”
Section: Commentmentioning
confidence: 95%
“…Peripheral globules are occasionally seen in melanoma. In a recent dermoscopic study of the morphology and distribution of peripheral globules in melanocytic lesions, Reiter et al 6 suggested that lesions with asymmetrically distributed globules or globules with varying shapes, sizes, and colors should be biopsied or closely monitored–especially pigmented lesions on the extremities—as they may be signs of an incipient melanoma.…”
Section: Commentmentioning
confidence: 99%
“…In this research, we have used two datasets to train and evaluate the performance of proposed system. First one is International Skin Imaging Collaboration (ISIC) which is largest publicity available dataset with considerable amount of instances 45 . It contains three different classes having label of melanoma, nevus and SK.…”
Section: Datasetsmentioning
confidence: 99%
“…Recent studies confirmed that regular peripheral globules are a dermoscopic feature that is mostly associated with benign melanocytic lesions. Melanocytic lesions with atypical or asymmetrically distributed peripheral globules, especially when located on the extremities, should raise suspicion for malignancy [81].…”
Section: Dermoscopic Featuresmentioning
confidence: 99%